Does International Criminal Court have Jurisdiction over the Destruction of Cultural Property by the Islamic State of Irac and Syria? - Bayu Sujadmiko; Desia Rakhma Banjarani; Rudi Natamiharja; Desy Churul Aini (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2021)
The cultural property becomes objects of destruction in armed conflicts, such as Syria and Iraq, which were carried out by ISIS squads (Islamic State of Iraq and Syria). For ISIS’s actions, the ICC should judge ISIS. However, new problems will arise regarding the jurisdiction of the ICC to judge ISIS. Based on the explanation of this background, the question will arise: How are humanitarian law regulations related to protecting cultural property during armed conflict? And what is the regulation of the ICC’s jurisdiction over the protection of cultural property in armed conflict by ISIS? The research in this article is normative legal research with the statue approach. According to humanitarian law, the research results show that the regulations relating to the protection of cultural property during armed conflict are contained in the 1954 Hague Convention, Additional Protocol I and Additional Protocol II of the Geneva Conventions of 1977. The destruction of cultural property carried out by ISIS is included in war crimes, one of the Rome Statute material jurisdictions. In this case, the Rome Statute applied by the ICC has juridical power to uphold justice and punish, including war crimes committed by ISIS. For the destruction of various cultural property in Iraq and Syria, ISIS can be judge by the ICC through a referral by the UN Security Council based on the provisions stipulated in the 1998 Rome Statute.